2015
DOI: 10.1080/21655979.2015.1048050
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus phytases: Current status and future prospects

Abstract: Phytases catalyze the hydrolysis of phytic acid in a stepwise manner to lower inositol phosphates, myo-inositol (having important role in metabolism and signal transduction pathways), and inorganic phosphate. These enzymes have been widely used in animal feed in order to improve phosphorus nutrition and to decrease pollution in animal waste. Compared to previously described phytases, the phytase (PhyL) from Bacillus licheniformis ATCC 14580 has attractive biochemical properties which can increase the profitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…A considerable amount of soil phosphorus is also found in the form of phytate (inositol phosphate) which is a complex of the phosphorus with other minerals (Findenegg and Nelemans 1993). Most of the Bacillus species identi ed in this study have been reported to produce phytase, an enzyme which cleaves phytate into soluble form (Borgi et al 2015). The abundance and e cacy of phytase producing microbes has been already assessed in tea garden soils of NE India (Pramanik et al 2014).…”
Section: Discussionmentioning
confidence: 76%
“…A considerable amount of soil phosphorus is also found in the form of phytate (inositol phosphate) which is a complex of the phosphorus with other minerals (Findenegg and Nelemans 1993). Most of the Bacillus species identi ed in this study have been reported to produce phytase, an enzyme which cleaves phytate into soluble form (Borgi et al 2015). The abundance and e cacy of phytase producing microbes has been already assessed in tea garden soils of NE India (Pramanik et al 2014).…”
Section: Discussionmentioning
confidence: 76%
“…These host genes are capable of metabolizing imino and amino acids [ 50 ]. These strain properties have been widely studied and applied to various bio-chemical industrial fields as a detergent agent [ 52 ], α-amylase [ 58 , 59 ], peptide antibiotics [ 60 , 61 ], fungal pathogens inhibitors [ 62 ], β-mannanase [ 63 , 64 ], cycloglucosyltransferase [ 65 ], pectinase [ 66 , 67 ], pentosanase [ 68 ], and phytase [ 54 , 69 , 70 ]. Although several B. licheniformis studies have contributed to better understanding of the strain, the following aspects of the enzyme have yet to be examined: the cloning of B. licheniformis cellulase genes, its E. coli cell-surface display, and numerous enzymatic characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The futuristic approach will develop economic and novel bio‐engineered phytase enzymes for simultaneous phytic acid degradation. Acid phosphatase/phytase 2 (appA2) from Escherichia coli , PhyL phytase from Bacillus licheniformis ATCC 14580, phytase from Weissella halotolerans are some examples of bio‐engineered phytase enzymes found to be effective against phytic acid (Borgi, Boudebbouze, Mkaouar, Maguin, & Rhimi, 2015; Demir, Şenol Kotan, Dikbaş, & Beydemir, 2017; Pakbaten et al, 2019). However, it requires human trials and prior approval by several health organizations for commercial use.…”
Section: Economic Aspects and Future Directionsmentioning
confidence: 99%
“…are some examples of bio-engineered phytase enzymes found to be effective against phytic acid (Borgi, Boudebbouze, Mkaouar, Maguin, & Rhimi, 2015;Demir, S ¸enol Kotan, Dikbas ¸, & Beydemir, 2017;Pakbaten et al, 2019). However, it requires human trials and prior approval by several health organizations for commercial use.…”
Section: Economic Aspects and Future Directionsmentioning
confidence: 99%